1998
DOI: 10.1006/dbio.1998.8866
|View full text |Cite
|
Sign up to set email alerts
|

Ectoderm Cell–ECM Interaction Is Essential for Sea Urchin Embryo Skeletogenesis

Abstract: Paracentrotus lividus sea urchin nectin (Pl-nectin) is an extracellular matrix (ECM) protein of the sea urchin embryo on the apical surface of the ectoderm and has been shown to be an adhesive substrate for embryonic cells. A monoclonal antibody (McAb) to Pl-nectin was generated that inhibits the adhesion of blastula cells to Pl-nectin-coated substrates in an in vitro functional assay. To examine for possible in vivo functions of Pl-nectin, Fab fragments (Fabs) of Pl-nectin McAb were added to early blastulae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 7 publications
2
45
0
Order By: Relevance
“…Cell fates are fully specified by the blastula-early gastrula stage of development, when cells have begun to express particular sets of territory-specific genes (Davidson et al, 1998). Although maternal determinants are required for founder cell specification during development, interactions between the PMCs and external cues derived from the ectoderm specify many phases of the skeleton formation (Armstrong et al, 1993;Ettensohn & Malinda, 1993;Guss & Ettensohn, 1997;Zito et al, 1998). The blastula stage is characterized by the presence of a large fluid-filled blastocoels, surrounded by a single layer of cells.…”
Section: Sea Urchin Embryonic Developmentmentioning
confidence: 99%
“…Cell fates are fully specified by the blastula-early gastrula stage of development, when cells have begun to express particular sets of territory-specific genes (Davidson et al, 1998). Although maternal determinants are required for founder cell specification during development, interactions between the PMCs and external cues derived from the ectoderm specify many phases of the skeleton formation (Armstrong et al, 1993;Ettensohn & Malinda, 1993;Guss & Ettensohn, 1997;Zito et al, 1998). The blastula stage is characterized by the presence of a large fluid-filled blastocoels, surrounded by a single layer of cells.…”
Section: Sea Urchin Embryonic Developmentmentioning
confidence: 99%
“…Without such a load-transfer mechanism, the individual platelets of the minerals would be exposed to extremely large mechanical loads and become more susceptible to mechanical failure [40,[55][56][57]. And the interactions between collagen bundles and fibrils, which are organic-organic interactions, are also important because [58], (c) Ji and Gao [66], (d) Sun and Bhusan [67], (e) Wilt [68], and (f) Zito et al [69].) the fiber bundles themselves are decorated by molecules that are electrostatically interacting, the so-called sacrificial bonds between bundles, and allows the bundles to shear between other bundles [58][59][60][61].…”
Section: Organic-inorganic Interfacesmentioning
confidence: 99%
“…Embryos were cell surface biotinylated as described by Zito et al (1998). Briefly, embryos were washed twice in ice-cold MFSW and then incubated in a biotinylation reagent (ECL Protein Biotinylation Kit, Amersham) at 4°C for 30 min, according to manufacturer's instructions.…”
Section: Cell Surface Biotinylationmentioning
confidence: 99%
“…A number of ECM proteins have been identified in the hyaline layer, including Pl-nectin, which was originally purified from Paracentrotus lividus eggs and shown to be localized to the apical surface of cells of the ectoderm and endoderm germ layers (Alliegro et al, 1988;Matranga et al, 1992). This ECM protein is also involved in indirect signaling between ectoderm and mesoderm germ layers (Zito et al, 1998). Indeed, we have shown that ectoderm cells must interact with Pl-nectin in the hyaline layer to enable permissive signals that are necessary for skeletogenic mesenchyme in the blastocoel to correctly grow and pattern the skeleton (Kiyomoto et al, 2004;Zito et al, 1998Zito et al, , 2000Zito et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation